CD19+CD20−CD27hi IL‐s10‐producing B cells are overrepresented in R‐CHOP‐treated DLBCL patients in complete remission. (September 2016) - Qiu, Huiying; Li, Junguo; Feng, Zhenjun; Yuan, Joanna; Lu, Jie; Hu, Xiaoxia; Gao, Lei; Lv, Shuqing; Yang, Jianmin; Chen, Lei
Summary: Treatment of diffuse large B cell lymphoma (DLBCL) with rituximab, an anti‐CD20 monoclonal antibody, has resulted in significantly improved patient responses with longer event‐free intervals and higher overall survival rates. However, since rituximab depletes all CD20‐expressing cells, including noncancerous B cells, the effects of rituximab on the normal immunity of DLBCL patients under remission need to be examined. Here, we observed that DLBCL patients under remission contained significantly lower frequencies of total B cells, with a significantly overrepresented interleukin (IL)‐10‐producing B cell (B10) population in the peripheral blood. Further examination confirmed that a large fraction of B10 cells was CD20 − CD27 hi plasmablasts, possibly explaining the persistence of B10 cells after R‐CHOP treatment. We also observed that the percentage of B10 cells in DLBCL patients in remission gradually reduced during the first year of achieving complete remission, primarily due to the replenishment of non‐B10 B cells. Despite this, the percentage of B10 cells in DLBCL patients after 1 year of achieving complete remission was still higher than that in controls. CD4 + and CD8 + T cells cocultured with B10‐enriched B cells secreted significantly lower levels of proinflammatory cytokines IFN‐g and TNF‐a, compared to those incubated with B10‐depleted B cells. Together, our data observed a long‐lasting overrepresentation of B10 cells in DLBCL patients under remission. Whether this change could impact on the overall anti‐tumor immunity during remission requires further studies.